Strategi Komunikasi Pemasaran Melalui Facebook (Studi Kasus pada Pengusaha Kue Kering Alissa Cookies) - Maulida Dwi Kartikasari; Mursyidah Dwi Hartati (JBIMA (Jurnal Bisnis dan Manajemen), 2018)
This research is aimed to find out how marketing strategy done by Tegal businessman "Alissa Cookies". Starting in 2017 Alissa Cookies” uses Facebook as a marketing strategy. This research uses a qualitative method with descriptive qualitative type. This study is focused on the implementation of Facebook as a marketing communications strategy at Alissa Cookies. From the study, it was obtained a comprehensive impact on the use and accompanied by the resulting result. The results show that Facebook is a very helpful strategy in marketing. Often promoting both product, business, and innovation through Facebook not only increases sales, but many benefits are gained. The benefits are information, increasing business partners, and the trust of the community. The amount of profit earned, of course, not only increases the sales but increases in sales every day.